Implementasi Sistem Informasi Supply Chain Management (SCM) Berbasis Web pada Franchise Ayam Super Fried Chicken - Raafi Muhammad Raafi Juliyanto; M. Teguh Prihandoyo; Yerry Febrian Sabanise (Journal of Applied Informatics Science, 2026)
The Ayam Super Fried Chicken franchise previously relied on manual, message-based communication to order raw materials from branch partners to the central warehouse, which frequently caused inaccurate stock records, delayed payment verification, and limited real-time visibility for the business owner. This study aims to design and implement a web-based Supply Chain Management (SCM) information system that automates supply-chain coordination and payment validation for the franchise. The system was built using the Laravel framework, a MySQL database, and Tailwind CSS for the interface, and it integrates the Midtrans payment gateway to automatically verify partner payments. The Waterfall model guided the development process, covering requirement analysis, system design using the Unified Modeling Language (UML), implementation, testing, and maintenance, while Black Box Testing was used to validate system functionality. Testing across four functional modules-authentication, transactions and payment, shipment management, and reporting and security-showed that all eleven tested scenarios ran as expected. The resulting system streamlines raw-material procurement between the central office and branch partners, secures financial transactions through automatic payment verification, and provides real-time operational transparency for franchise management through an analytics dashboard and an activity audit log.